No One Can Serve Two Masters: Corporate and Securities Law After Enron - Joel Seligman (Washington University Law Quarterly, 2002)
A widespread belief appears to have evolved in the United States financial community that time honored rules such as those that discourage conflicts of interest are quaint and easily circumvented. Too frequently, in recent years, sharp practitioners in business, investment banking, accounting or law appear to have challenged the fundamental tenets of “full disclosure of material information” or “fair presentation of accounting results.” A deterioration in the integrity of our corporate governance and mandatory disclosure systems may well have advanced, not because of a novel strain of human cupidity, but because we had so much success, for so long, that we began to forget why fundamental principles of full disclosure and corporate accountability were long considered essential.
Keywords: Securities fraud; Business ethics; Law reform; Enron Corp.